Hydrogels loaded with atenolol drug metal–organic framework showing biological activity - Du Juan; Fan Limei; Fu Jinfeng (Science and Engineering of Composite Materials, 2023)
Using the starting reactants of Zn(OAc)2 and 2-mercaptonicotinic acid (H2L), we successfully synthesized a fresh Zn(ii) compound, that is, [Zn3(L)3]n (1), under hydrothermal conditions and then successfully loaded with atenolol. Hualuronic acid/carboxymethyl chitosan hydrogels loaded with atenolol drug metal–organic framework were prepared based on a chemical synthesis method. The microscopic morphology of the hydrogels was investigated, and scanning electron microscopic results showed that the hydrogels had a highly porous morphology with good penetration between the pores. For the new hydrogels, the enzyme-linked immunosorbent assay detection was conducted, and the production of sVCAM-1 and TNF-a in vascular endothelial cells was determined. Besides, the levels of inflammatory response in the vascular endothelial cells were also determined with the real-time reverse transcriptase polymerase chain reaction assay.